Development of Road Safety Discipline: Cultivation Strategies for Youth in School is Kamphaeng Phet Province - Chommanarttikorn, Jitti; Polprasert, Pajaree; Chutan, Nopakhun (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The research aims 1) to study the behaviors and causes of road safety disciplines of youth in schools in Kamphaeng Phet Province, 2) to study the conditions, problems, and factors related to the cultivation of road safety disciplines for youth in schools, 3) to develop strategic cultivation of road safety disciplines for youth in schools, and 4) to evaluate strategic cultivation of road safety disciplines for youth in schools. The research was conducted in 4 steps. In Step 1, the behaviors and causes of road safety disciplines of youth were surveyed with 381 people in 3 behavior aspects: regulatory offences, risk behavior, and negligence behavior, and examined together with the causes of road safety disciplinary actions of the youth in terms of family, physical, psychological, social, and environmental aspects. In Step 2, the data collection methods used were questionnaires and group chats to explore the conditions, problems, and factors related to the cultivation of road safety disciplines for youth in schools. In Step 3, the process of developing road safety discipline strategies for youth in schools was organized by 3.1) interviewing 4 schools that successfully implemented road safety disciplines, 3.2) organizing Environmental Analysis (SWOT Analysis) workshops with 13 experts, 3.3) drafting cultivation strategies for road safety disciplines with 11 experts, and 3.4) examining the draft by 13 experts. In Step 4, the road safety discipline strategies were evaluated by 22 experts. The results showed: The behaviors and causes of road safety disciplines of youth in schools in Kamphaeng Phet Province were found that most young people drive/ride without driving/riding licenses because family conditions require them to drive/ride to schools. They do not wear helmets for the short ride because they follow their friends, and their schools are nearby. They always accelerate to pass yellow traffic lights. In addition, on the clear roads, they tend to drive faster and switch lanes frequently. They also overtake on the solid white line or on bridges to pass slower-driving cars. Within the family aspect, it was found that parents are not always good role models and neglected to educate the youth basic driving rules. Moreover, the youth thought that they were always helped by their parents when they violate traffic rules. Physically, some youth still drive/ride even when they have vision and hearing impairments. Mentally, some youth have the mindset that following the traffic rules is a waste of time. Environmentally, it was found that the related authorities and departments do not take good care of road conditions, for example, trees, billboards, traffic signs. Most conditions, problems and factors related to the cultivation of road safety discipline for young people in the school were moderate. The key problems were that the traffic police educators are insufficient, unreliable, and unfriendly. The other main factors included the attitudes toward their friends and families. The road safety discipline strategies for youths in schools were developed under the concepts of vision, mission, and purpose to enhance the management system, budget, innovation, technology, public relations system, and the monitoring and evaluation process in implementing road safety disciplines for youth in schools in Kamphaeng Phet Province. Evaluation of the development of road safety discipline strategies was found consistent, suitable, feasible, and beneficial at the highest level.